Intuitionistic fuzzy edas method: an application to solid waste disposal site selection - Kahraman, Cengiz; Ghorabaee, Mehdi Keshavarz; Zavadskas, Edmundas Kazimieras; Onar, Sezi Cevik; Yazdani, Morteza; Oztaysi, Basar (Journal of Environmental Engineering and Landscape Management, 2017)
Evaluation based on Distance from Average Solution (EDAS) is a new multicriteria decision making (MCDM) method, which is based on the distances of alternatives from the average scores of attributes. Classical EDAS has been already extended by using ordinary fuzzy sets in case of vague and incomplete data. In this paper, we propose an interval-valued intuitionistic fuzzy EDAS method, which is based on the data belonging to membership, nonmembership, and hesitance degrees. A sensitivity analysis is also given to show how robust decisions are obtained through the proposed intuitionistic fuzzy EDAS. The proposed intuitionistic fuzzy EDAS method is applied to the evaluation of solid waste disposal site selection alternatives. The comparative and sensitivity analyses are also included.